The Impact of Financial Information Transparency on Corporate Governance Effectiveness - Wang, Jingxuan (Transactions on Economics, Business and Management Research, 2024)
In today’s rapidly changing business environment, financial information transparency has become a key indicator for measuring the quality of corporate governance. This paper introduces the basic concept of financial information transparency, the relationship between financial information transparency and corporate governance, and focuses on the impact of financial information transparency on stakeholders, challenges and strategies to improve financial information transparency, and finally predicts the development trend of financial information transparency. It is hoped that the analysis of these issues will be helpful in improving the transparency of corporate financial information and promoting more effective and transparent corporate governance practices.